Transformational Leadership in Building Organizational Citizenship Behavior - Hilyatun Nisa; Faizul Mubarak (Journal of Research in Educational Management, 2022)
This study aims to analyze transformational leadership in building organizational citizenship behavior at MI Raudhatul Mustariyah Pasuruan. The benefits of OCB behavior for the organization and the employees themselves, among others, are that it can increase employee turnover rates, can make employees longer in work. This study uses qualitative methods, the type of research is through phenomena, which seeks to understand related phenomena that are implemented and grow and try to describe the findings in the field, with data collection techniques in the form of observations and interviews. Information analysis is carried out through the stages of presenting information, reducing information and drawing conclusions. The location of the research is MI Raudhatul Mustariyah Pasuruan. Based on the results of the research conducted, which explains that transformational leadership in building organizational citizenship behavior at MI Raudhatul Mustariyah Pasuruan is shown in the characteristics of transformational leadership where leadership is a person's ability to influence others (subordinates) in such a way, while the characteristics of transformational leadership are: idealized influence ( idealized influence), inspirational motivation (inspirational motivation), intellectual stimulation (intellectual stimulation) and individualized consideration (individual considerations).